2D MXene Ti3C2Tx nanosheets in the development of a mechanically enhanced and efficient antibacterial dental resin composite - Hu, Yingzi; Xu, Zhiliang; Pu, Junmei; Hu, Lanping; Zi, You; Wang, Mengke; Feng, Xingmei; Huang, Weichun (Frontiers in Chemistry, 2022)
The bacterial accumulation at the margin of dental resin composites is a main cause of secondary caries, which may further lead to failure of prosthodontics. In this regard, 2D MXene Ti3C2Tx nanosheets (NSs) are, for the first time, incorporated into epoxy resin with different mass ratios (0, 0.5, 1.0, and 2.0 wt%) by solution blending and direct curing for dental applications. Compared to the pure resin, the as-fabricated MXene/resin composite not only exhibits improved mechanical and abrasive results but also displays gradually improved antibacterial activity with the MXene loading which can be further enhanced illuminated by natural light due to high photothermal efficiency of MXene. In addition, the cytotoxicity result demonstrates that the MXene-modified resin does not cause severe damage to the normal cells. It is foreseen that the novel MXene/resin nanocomposite could pave the way to new designs for high-performance nanocomposite with multifunctionalities to effectively protect dental healthy in daily life.